ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK BUMN DAN BANK SWASTA DI INDONESIA BERDASARKAN METODE RGEC PERIODE 2015-2019 - Annisa Syachrani; Sugiharti Binastuti (Politeknik Raflesia Press, 2021)
Abstrack-As an intermediary institution and support for the nation's economic activity, banks must pay attention to their health level. Information regarding the soundness of a bank is very much needed by various parties involved, both parties from within the bank itself and parties from outside the bank to evaluate the bank's performance in applying prudential principles, compliance with applicable regulations and risk management. This study aims to determine the comparison between state-owned and private banks, the performance of banks in Indonesia on NPL, LDR, GCG, ROA, ROE, and CAR. The population in this study were state-owned and private banks in Indonesia. The sampling technique was carried out at four state-owned banks and four private banks in Indonesia and quantitative data in the form of financial statements. The analysis technique used Normality Test, Paired t-test and Wilcoxon Signed Rank Test.The results of this study are that according to the Paired t-test NPL, ROA, ROE, and CAR there is no difference in the soundness of state-owned banks and private banks, but LDR experiences differences in the soundness of state-owned banks and private banks. According to the Wilcoxon Signed Rank Test, there is no difference in the soundness of state-owned banks and private banks.